Comparative Quantitative Assay of Apigenin and Luteoline Study of Different Market Samples of Bharangi (Clerodendrum Serratum Linn) w.r.t. UPLC (AYUSHDHARA, 2025)
Bharangi (Clerodendrum Serratum Linn) is one of ancient drug used in many preparations for treatment of many pathological conditions like Kasa, Shwasa, Jwara, Gulma, Aruchi, etc. That’s why there is need of pharmacognostical and phytochemical screening of different market samples of Bharangi (Clerodendrum Serratum Linn) with the help of UPLC study. Objectives: To undertake pharmacognostic and phytochemical screening of different market samples of roots of Bharangi (Clerodendrum Serratum Linn) and to compare the apigenin and Luteolin quantitatively in different market sample of root of Bharangi with the help of UPLC study. Materials and Methods: This was a laboratory-based study that included the analysis of different market samples of Bharangi (Clerodendrum Serratum Linn) in 3 phases, such as follows; a) Macroscopic and microscopic examinations with physio-chemical assessment involving the examination of ash value, pH water soluble extract, methanol - soluble external, acid insoluble ash and the extraction of volatile oil utilizing a clevenger apparatus. b) A qualitative phyto-chemical screening is conducted-demploying TLC method followed by phase 3 c) Which involves UPLC study. Results: The present showed that the market sample from Bengaluru had the highest quality of luteolin followed by Delhi and Rajasthan. All the three samples of Bharangi (Clerodendrum Serratum Linn) comprised both apigenin and luteolin with variations in both the quantity and this could be because of various factors such as soil properties, cultivation methods, environment, collection methods, extraction methods and age of plant. Conclusion: All the samples of Bharangi (Clerodendrum Serratum Linn) successfully fulfilled all the pharmacopoeia standards hence they are suitable for medicinal use.